Adverse reactions to foods (ARFS) in children: parental knowledge, awareness and behaviour - Asma Ali,; Hayati Mohd Yusof,; Chong, Set Lin (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study aimed to assess parental knowledge, awareness and behaviour on Adverse Reactions to Foods (ARF) and its relation to family’s quality of life. In this cross-sectional study, 120 parents of children with documented ARFs in Selangor were recruited. Of these parents, 63.3% and 50.8% exhibited low levels of knowledge and awareness of ARFs, respectively. In terms of dietary practices, 31.7% avoided possible allergenic foods during pregnancy. The study found that 66.7% of children followed the childhood immunization schedule and 32.5% had symptomatic ARFs onset at age 36 months and above. Seafood appeared to be the main cause of ARFs (68%). ARFs appeared to be triggered mainly by environmental factors as reported by 46.7% of respondents. Nearly 56% of parents reported emotional responses associated with caring for ARF children while 8.8% and 17.5% found that ARFs affected relationships with family members and social acquaintances, respectively. A positive association was observed between specific levels of ARF knowledge and parental educational levels (p < 0.05). This findings represent an attempt to provide information for public education in a practical manner that can help optimize and sustain health benefits and overall community well-being.